The laws of social organization - Johansen B., Oscar (Estudios de Administración, 1996)
The author posits the existence of certain regularities to be found in every social organization. In the present paper five of such regularities are identified, under the denomination of "laws of social organizations". Each of these establishes border lines that set limits or constraints for the designer of organizations, in a way similar to that of the laws of physics, chemistry and other scientific fields.